Publicly available surveillance data on tick-borne encephalitis in Europe, 2023 - Angulo, Frederick J․; Halsby, Kate; Davidson, Alexander; Ravikumar, Saiganesh; Pilz, Andreas; Stark, James H.; Moïsi, Jennifer C. (Ticks and tick-borne diseases, 2024)
•TBE, TBEV infection, or acute/viral meningitis/encephalitis is a reportable condition in 37 European countries and 26 countries reported cases in 2020–2023.•Twenty-four countries reported on TBE cases to ECDC in 2020.•Standardization of surveillance would enhance the understanding of TBE disease burden in Europe. The European Centre for Disease Prevention and Control (ECDC) defines a case of tick-borne encephalitis (TBE) as an infection by the TBE virus (TBEV) with clinical manifestations of central nervous system inflammation (e.g., meningitis, encephalitis). To better understand the TBE surveillance landscape, online searches were conducted to determine if cases of TBE, TBEV infection, acute meningitis or encephalitis, or viral meningitis or encephalitis were subject to statutory reporting in European countries in 2023. In countries with statutory reporting, notification responsibility and available information on surveillance-reported cases were determined. The number of TBE cases reported to ECDC were compared with the number of cases recorded in national surveillance reports. Of 44 countries of the Europe Region of the United Nations, 37 (84 %) mandated statutory reporting of cases of TBE, TBEV infection, or acute/viral meningitis/encephalitis. Twenty-six (87 %) of 30 countries with identified surveillance reports recorded TBE cases in 2020–2023. Of these countries, 17 (65 %) required TBE reporting by clinicians and laboratories, 5 (19 %) by clinicians only, and 4 (15 %) by laboratories only. Twenty-four countries reported on TBE cases to ECDC in 2020; however, surveillance for TBE in Europe is heterogeneous. Standardization of TBE surveillance would enhance the understanding of TBE disease burden in Europe.